INTEGRATION OF THE QUIZIZZ PLATFORM IN THE EVALUATION OF ISLAMIC VALUE-BASED LEARNING IN ELEMENTARY SCHOOLS - Faisal Asha; Devi Sulaeman; Mia Audina Musyadad; Vina Febiani Musyadad; Asep Supriatna Asep (Indonesian Journal of Elementary Education (IJETE), 2026)
Digital transformation in elementary education demands technology integration that is not only oriented towards learning effectiveness but also towards strengthening character values. Learning evaluation, as a crucial part of the educational process, needs to be designed adaptively without neglecting the internalization of Islamic values. This study aims to analyze and describe the integration of the Quizizz platform in evaluating Islamic value-based learning at SDN Palumbonsari I, East Karawang District. The study used a qualitative approach with a case study type. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed interactively through reduction, presentation, and drawing conclusions. The results show that the integration of Islamic values ​​was carried out systematically through three stages: evaluation planning by incorporating value indicators into learning tools, implementation of values ​​in question design and digital feedback, and post-evaluation reflection in class. Digital features were utilized not only to display scores but also to convey moral messages that support Islamic character formation. In practice, digital evaluation functions as a cognitive measurement instrument as well as a means of habituating values. The implications of this research confirm that the use of digital platforms in evaluation can be directed as a medium for internalizing values ​​if it is designed in a structured manner and supported by the teacher's pedagogical commitment.